Financial Administration of the Internal Revenue Allotment (IRA) Among Barangays in Bayugan City, Agusan de Sur, Philippines - Marecon Viray (Kajian Asia Pasifik, 2021)
In the Republic Act 7160 otherwise known as the Local Government Code of 1991 has considerably altered the nature and participation of the local government units in the pursuit of national development. Considered that the barangays is the smallest political system in the Philippines were given the responsibility and authority to implement barangay development of their Internal Revenue Allotment. Hence, despite the allocation for the Internal Revenue Allotment (IRA) to barangays for the development, problems affecting the administration of such fund are so obvious. The system of administering the barangay development programs has evolved along with the changing structure of our government. The study aimed to describe the financial administration of the Internal Revenue Allotment (IRA) of barangays in Bayugan City. The cross-sectional survey research design was used frequency counts and distributions were utilized to present and analyze the data gathered. The sample barangays were taken through purposive sampling using income as the main criterion. Primary and secondary data thru the questionnaire and documents. The allocations of the 43 barangays of Bayugan City tend to increase. The barangays had also sourced their funding needs from sources other than IRA or alternative sources. Recommendations, there must be an in-depth review on the procedure of allocating the IRA among barangays in Bayugan City. Likewise, an in-depth review on the required itemized budget be carried out of expenditures for barangays must be carried out such that barangays prone to calamities may have options in regard to their annual allocation; The barangay officials should strengthen further the participation of all barangay constituents in determining the priority projects and similar studies should be conducted in order to know further the extent of the strengthens and weakness.